Comparative study of glycerol conversion to polyglycerol via conventional and microwave irradiation reactor. (2019) - Sajid, Muhammad; Ayoub, Muhammad; Uemura, Yoshimitsu; Yusup, Suzana; Saleem, Mahmood; Abdullah, Bawadi; Khan, Asad U.
Abstract: The production of biodiesel and oleochemicals has been increasing around the world for more than a decade. This increased production is creating a heap of low-value glycerol as a byproduct. Thus, the glycerol supply is totally independent to its demand now a day due to available this huge glut of biodiesel drive glycerol. This unique situation has led the glycerol price low, which is also a factor to hinder the economical price of biodiesel. Now glycerol is used as a raw material for conversion into the useful product (polyglycerol) due to its low cost, availability and enormous application of polyglycerol in food, polymer, cosmetic and pharmaceutical industries. The comparative study showed that the optimize etherification process for 90% conversion of glycerol examined into polyglycerol under microwave irradiations as a heat source within 3 hours by using Li/MK10 catalyst and 80% conversion by conventional heating under a solvent-free conditions within 8 hours by using homogenous catalyst Na2 CO3 .